Exploring dyadic management of nutrition care throughout and beyond head and neck cancer treatment. Issue 19 (24th October 2021) - Hiatt, Joanne; Young, Adrienne; Brown, Teresa; Banks, Merrilyn; Bauer, Judith
Abstract: Aims and Objectives: To identify how patients and carers collaborate to manage nutrition care throughout and beyond head and neck cancer (HNC) treatment as a step towards identifying changes to service delivery that are inclusive of the needs of the patient–carer dyad. Background: Research in the field of dyadic interventions in cancer care is emerging, and there has been little work exploring patient–carer dyad needs in the provision of nutrition care in HNC. Design: A qualitative study design was used. Methods: Narrative interviews were completed with 13 patients and 15 carers over a 12‐month period (prior to treatment commencing, and 2 weeks, 3 months and 12 months post‐treatment completion). Deductive analysis of interview transcripts was performed using directed content analysis guided by the Theory of Dyadic Illness Management (TDIM). COREQ guidelines were used. Results: Seven themes across four TDIM constructs were identified: (1) understanding and adapting to physical challenges impacting nutrition intake, (2) adjusting to emotional impact of changes to eating and drinking, (3) providing practical support, (4) intrapersonal characteristics, (5) interpersonal characteristics, (6) healthcare culture and (7) managing carer burnout. Conclusion: This study highlights the importance of healthcare professionals recognising the patient and carer dyad as a team to enhance engagement in nutrition care and to ensure that their physical and psychological support needs across the cancer continuum are met. Relevance to clinical practice: It is important that healthcare professionals understand information and support needs and preferences within patient–carer dyads prior to HNC treatment commencing and adapt care and interventions based on their changing needs throughout and beyond the treatment period.